TANGGUNG JAWAB ORANG TUA TERHADAP ANAK SETELAH PERCERAIAN (STUDI KASUS PADA PENGADILAN NEGERI KUALA TUNGKAL) - Abdul Hariss (Jurnal LEX SPECIALIS, 2012)
Abstract One of the issues that arise in divorce life is the maintenance of the child, where the child can no one wants to take care of or between the two spouses want each other to take care or control of the child. To demonstrate responsibility for the maintenance of the child, the husband and wife were divorced sometimes scrambling to master, eventually a dispute between the two. With a dispute for control of the child resulting solution should be up to the courts. Win the defeat of the father or mother fighting over her, still the loser did not escape his responsibilities to his son, but the biggest responsibility is to win the struggle on the part of the child. In fact, it is not infrequently the case memperebut party won control of the child even less ability to provide for their children, while the parents as the losing party was spurious to help and accountability. Key Note : Responsibility, Divorce